Relationships between Body Size and Testicular Morphometric Traits of Mature Rams of Djallonke and Ouda Breeds Reared in North Benin - KOUTINHOUIN, G. BENOÎT; TOUGAN, P. ULBAD; BOKO, KADOÉITO CYRILLE; ZANNOU, M. SERGE; HANZEN, Christian (My University, 2017)
The study aims to determinethe correlations between testicular and body morphometric traits ofDjallonkeand Oudasheep breeds reared on natural pasture in Benin. Data were collected on 70 mature rams including 45Djallonke rams and 25Ouda rams, from January 2015 to September 2016. These data were analyzed with SAS software (2006). It appears that in Djallonke rams, apart from scrotal length, mean testes density and mean epididymal density the all other testicular morphometric parameters were strongly and positively associated with the live weight (0.45≤r≤0.90; P<0.001). The whither’s height was fairly and positively correlation with the chest circumference and the pelvis length (r=0.45 and 0.49 P<0.01), but strongly and positively associated with the scapulo-ischium length, shoulder width, scrotal length, scrotal circumference, paired testes weight, mean testes length, testes diameter, mean testes volume, paired epididymal weight, mean epididymal length and mean epididymal volume (0.55≤r≤0.71; P<0.001). Furthermore, the scrotal length was very highly and positively associated with the scrotal circumference, paired testes weight, mean testes length, testes diameter, mean testes volume, paired epididymal weight, mean epididymal length and mean epididymal volume (0.73≤r≤0.78; P<0.001). The scrotal circumference was strongly and positively associated with the paired testes weight, mean testes length, testes diameter, mean testes volume, paired epididymal weight, mean epididymal length and mean epididymal volume (0.68≤r≤0.93; P<0.001). As for Ouda sheep breed, the whither’s height was weakly and positively with pelvis length, paired testes weight, mean testes length and mean epididymal density (0.20≤ r ≤0.39; P<0.05), but strongly and positively associated with the mean epididymal length and mean epididymal volume (r=0.15 and 0.27; P<0.001). Scrotal circumference, paired testes weight, mean testes length, testes diameter, mean testes volume, paired epididymal weight, mean epididymal length and mean epididymal volume were strongly and positively associated with the scrotal length (0.66≤r≤0.74; P<0.001). Scrotal circumference was strongly and positively correlated with the paired testes weight, mean testes length, testes diameter, mean testes volume, paired epididymal weight, mean epididymal length and mean epididymal volume (0.74≤r≤0.93; P<0.001). Furthermore, the paired testes weight was strongly and positively associated with the mean testes length, testes diameter, mean testes volume, paired epididymal weight, mean epididymal length and mean epididymal volume (0.81≤r≤0.99; P<0.001). Therefore, improve body size will improve the reproductive organ traits as a correlated response.
Keywords: Benin; Djallonke; Ouda; Correlations; Sheepgonads; Morphometric traits